2016
DOI: 10.1021/jacs.6b07444
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Photochemistry of Triplet 1,3-Dimethylpropynylidene (MeC3Me)

Abstract: Photolysis (λ > 472 nm) of 2-diazo-3-pentyne (11) affords triplet 1,3-dimethylpropynylidene (MeC3Me, (3)3), which was characterized spectroscopically in cryogenic matrices. The infrared, electronic absorption, and electron paramagnetic resonance spectra of MeC3Me ((3)3) are compared with those of the parent system (HC3H) to ascertain the effect of alkyl substituents on delocalized carbon chains of this type. Quantum chemical calculations (CCSD(T)/ANO1) predict an unsymmetrical equilibrium structure for triplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Alkynyl diazo compounds are important precursors of alkynyl carbenes, and their reaction mechanism upon photolysis and thermolysis has been a subject of numerous physicochemical studies due to their unusual electronic structure . Free alkynyl carbenes are also intermediates in the chemistry of interstellar space and polymer photochemistry .…”
mentioning
confidence: 99%
“…Alkynyl diazo compounds are important precursors of alkynyl carbenes, and their reaction mechanism upon photolysis and thermolysis has been a subject of numerous physicochemical studies due to their unusual electronic structure . Free alkynyl carbenes are also intermediates in the chemistry of interstellar space and polymer photochemistry .…”
mentioning
confidence: 99%
“…In general, ethynylcarbenes are relevant in astrochemical processes , and can even be used synthetically. The electronic structure of parent ground-state triplet propynylidene (HCCCH) has been explored in numerous experimental and computational studies with the result that both terminal carbons are equivalent in terms of their reactivity. The photoreaction of propynylidene with triplet dioxygen provides another entrance channel to the C 3 H 2 O PES as shown in a study by Wierlacher et al, who observed 2 besides the corresponding dioxirane and carbonyl oxide . Other triplet ground-state derivatives of propynylidene have been investigated spectroscopically and they display similarly delocalized electronic structures. In contrast, singlet ethynylcarbenes (such as 1 ) can best be represented by a localized carbene center in α-position to a localized CC bond …”
mentioning
confidence: 99%
“…Carbenesunstable compounds of divalent carbontogether with ions and free radicals are one of the main classes of highly reactive intermediates that determine the direction of chemical reactions and the structure of the resulting products . They have been well known for almost 70 years and have been a subject of numerous chemical and physicochemical studies. In recent years, considerable attention has been paid to the study of ethynylcarbene- conjugated triplet carbon chain molecules, whose electronic structure and reactivity have been explored by different spectroscopic and computational methods. These species are of interest due to their unusual electronic structure, as well as their participation as intermediates in many important processes in astronomy , and polymer photochemistry. Base-induced generation of different alkynylcarbenes and their reactions with various organic substrates have been the subjects of our previous works. Ten years back, a highly delocalized triplet carbene comprising both vinyl and ethynyl groups at the carbene center, 5-methylhexa-1,2,4-triene-1,3-diyl, was generated in a low-temperature Ar matrix upon UV photolysis of 5-ethynyl-3,3-dimethyl-3 H -pyrazole and studied by IR and ESR spectroscopies. , It was shown that two major photolytic rearrangements of this carbene represent reactions characteristic of vinyl carbenes, resulting in the formation of 1-ethynyl-3,3-dimethylcyclopropene and 3 E -2-methylhexa-1,3-dien-5-yne. A minor reaction, typical of ethynylcarbenes, leads to the formation of singlet 2-(2-methylpropenyl)­cyclopropenylidene.…”
Section: Introductionmentioning
confidence: 99%